2015
DOI: 10.1186/s12879-015-1095-5
|View full text |Cite
|
Sign up to set email alerts
|

Proadrenomedullin and copeptin in pediatric pneumonia: a prospective diagnostic accuracy study

Abstract: BackgroundCommunity-acquired-pneumonia is the leading cause of child mortality worldwide. Very few studies have explored the predictive value of Proadrenomedullin and Copeptin in pediatric severe pneumonia and bacteremia.MethodsProadrenomedullin and Copeptin were assessed as predictors for complicated community-acquired pneumonia (bacteremia, empyema) in 88 children aged 0 to 16 years presenting to the pediatric emergency department, using B.R.A.H.M.S. Kryptor Compact pro-ADM and Copeptin with the TRACE techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
3
21
1
Order By: Relevance
“…In pediatric patients with uncomplicated CAP and CAP complicated with bacteremia and/or empyema, copeptin was not identified as a relevant biomarker [9]. However, this is the same secondary analysis that investigated sTREM-1 and copeptin and was not associated with statistical power calculation.…”
Section: Copeptinmentioning
confidence: 76%
See 1 more Smart Citation
“…In pediatric patients with uncomplicated CAP and CAP complicated with bacteremia and/or empyema, copeptin was not identified as a relevant biomarker [9]. However, this is the same secondary analysis that investigated sTREM-1 and copeptin and was not associated with statistical power calculation.…”
Section: Copeptinmentioning
confidence: 76%
“…The evidence of proadrenomedullin to support the diagnosis of bacterial RTIs is inconsistent. One study with pediatric patients with complicated and bacteremia-associated pneumonia vs. pleural empyema showed 100% sensitivity and could accurately distinguish between these patient groups (AUROC >0.85) with a sensitivity and specificity comparable to CRP [9]. However, no specific statistical power calculation was performed as this study was a secondary analysis.…”
Section: Proadrenomedullinmentioning
confidence: 97%
“…A significant difference in ProADM median values was again found in complicated cases (0.18 vs. 0.08 nmol/L, p = 0.039) and in bacteraemic CAP (0.40 vs. 0.08 nmol/L, p = 0.02). A cut off of ProADM > 0,16 nmol/L had 100% sensitivity (95% CI 39.8-100.0) and 70% specificity (95% CI 58.7-79.7) for bacteraemia and a cut off of 0.16 nmol/L was as accurate as CRP <100 mg/L and better than band neutrophils (<1.5 G/L) or leucocytosis (<15 WBC/L) to rule out bacteraemia (sensitivity and NPV = 10%) [14].…”
Section: Pneumoniamentioning
confidence: 97%
“…All of the 323 studies screened and excluded were not relevant to the systematic review. There were 11 full text articles that underwent full review, and six studies were eligible for inclusion in the nal systematic review [18][19][20][21][22][23][24][25][26][27][28].…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the ve excluded studies four were excluded because the index test was Adrenomedullin and not MR-proADM and one study was excluded because it only reported the differences in cord blood concentrations of MR-proADM in newborns with and without risk factors for infection [24][25][26][27][28]. Two of the six eligible studies reported on adult and paediatric data [22,23].…”
Section: Study Selectionmentioning
confidence: 99%